Pemberian ASI dan Susu Botol pada Kejadian Early Childhood Caries (ECC) : Scoping Review - Fatimah Boenjamin Partakusuma; Narpadayita Pradipta Putri; Dhyani Widhianingsih (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Abstract: Early Childhood Caries (ECC) is a public health problem defined as the presence of one or more teeth with carious lesions in children aged 6 years or younger. ECC can affect a child's well-being, growth and quality of life. Factors such as poor oral hygiene, bacterial invasion, poor dietary habits, and the presence of enamel defects can contribute to lesion formation. The risk of ECC may also be due to breastfeeding or formula feeding overnight. The aim of this study to determine the role of breastfeeding and formula feeding through bottles on Early Childhood Caries (ECC). This Scoping Review was conducted according to Preferres Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and two database (PubMed and Google Scholar). The results showed that the initial search yielded 183 documents. After eliminating duplicate studies and screening full-text articles for eligibility (n = 35), we identified 7 studies that met the criteria for inclusion. The duration, frequency and night-time feeding of breast milk and bottle milk supported by other environmental factors may increase the risk of Early Childhood Caries (ECC).